2020
DOI: 10.1029/2020ef001485
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Driving Forces of India's Emissions From Production and Consumption Perspectives

Abstract: While India becomes one of the largest carbon emitters in the world with a high emission growth rate, existing studies fail to capture the recent trends and the key driving factors behind it. Here, by using multiregional input‐output analysis and structural decomposition analysis, we measure the contribution of factors to the changes of India's domestic consumption and trade‐related emissions. This study finds that India's per capita consumption has a significant raising effect on India's consumption‐based emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…From the perspective of MFOZs, this study focused on the spatiotemporal evolutionary characteristics. Carbon Emission Accounts and Datasets (CEAD; www.ceads.net.cn) previously published provincial-scale emissions from 1997 to 2017 across China, and its data have been used in much research [42][43][44]. For validating the results, we compared the carbon emissions in 2017 from CEAD (514.64 million tons) and this study (559.08 million tons), and found the error to be ~8%, which is acceptable.…”
Section: Resultsmentioning
confidence: 85%
“…From the perspective of MFOZs, this study focused on the spatiotemporal evolutionary characteristics. Carbon Emission Accounts and Datasets (CEAD; www.ceads.net.cn) previously published provincial-scale emissions from 1997 to 2017 across China, and its data have been used in much research [42][43][44]. For validating the results, we compared the carbon emissions in 2017 from CEAD (514.64 million tons) and this study (559.08 million tons), and found the error to be ~8%, which is acceptable.…”
Section: Resultsmentioning
confidence: 85%
“…Our assessment is based on a decomposition of the Kaya identity, a top-down model, which allows us to gain insight into all sectors and assess emissions at a broader economic level. Earlier studies using a decomposition analysis of historical consumption-based emissions found that investment effects on emissions in developing countries (mostly in China, and also in Mexico, India and Indonesia) are larger than those in developed countries (Liu et al, 2019), but that this influence has weakened in China in recent years, due to the reduction in government subsidies (Mi et al, 2017;Meng et al, 2019;Wang et al, 2020). Based on these past trends, we show that, over the coming decades, although China and others (e.g., Australia and Russia) see declining infrastructure expenditure, the persistence of historical trends in the evolution of consumption pattern (a gradual increase in the shares of construction and investment) contributes to emission increases in major emerging nations (e.g., Brazil, Mexico and India) in a significant way (Fig.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…Analysis of existing research shows that research literature on different countries and regions, departments, and driving factors is already quite comprehensive [4][5][6][7][8][9][10].Common driving factors include per capita GDP, digital economy, energy structure, carbon dioxide emission intensity, population size, technological level, urbanization level, industrial structureand energy intensity [11][12][13][14][15].Wang Zhi and others used SDA to study the driving factors of carbon emissions in India [5].Yang Jun and others used the extended LMDI method to construct regional contribution indices for different driving factors [7].Guo Jin et al conducted a study specifically targeting urbanization as a driving factor using Kaya's equation [10].However, the limitation of the above research is that it does not strictly define the concept of driving factors, and the selection of driving factors is conducted from a closed perspective.…”
Section: Introductionmentioning
confidence: 99%